Menggugah Imajinasi: Strategi Kreatif dalam Pembelajaran Agama Islam untuk Anak Tingkat Pemula - Siti Rofiqoh (Universitas Al-Amien Prenduan, 2021)
This research aims to explore Creative Strategies and their variations to stimulate imagination in Islamic religious learning for beginners. The study adopts a qualitative approach with a literature review type focusing on scholarly literature discussing the topic. The data sources used include scientific literature such as reference books and published journal articles. Content analysis is employed as the data analysis method. The results of this research indicate that creative strategies in Islamic religious learning for beginners have a significant positive impact. Creative strategies, such as Islamic teachings-based stories and role-playing games, have proven to create an engaging and inspirational learning environment.